Size-dependent bending, buckling and vibration of higher-order shear deformable magneto-electro-thermo-elastic rectangular nanoplates. (8th June 2017) - Gholami, Raheb; Ansari, Reza; Gholami, Yousef
Abstract: The aim of the present study is to propose a unified size-dependent higher-order shear deformable plate model for magneto-electro-thermo-elastic (METE) rectangular nanoplates by adopting the nonlocal elasticity theory to capture the size effect, and by utilizing a generalized shape function to consider the effects of transverse shear deformation and rotary inertia. By considering various shape functions, the proposed plate model can be reduced to the nonlocal plate model based upon the Kirchhoff, Mindlin and Reddy plate theories, as well as the parabolic, trigonometric, hyperbolic and exponential shear deformation plate theories. The governing equations of motion and corresponding boundary conditions of METE nanoplates subjected to external in-plane, transverse loads as well as magnetic, electric and thermal loadings, are obtained using Hamilton's principle. Then, as in some case studies, the static bending, buckling, and free vibration characteristics of simply-supported METE rectangular nanoplates are investigated based upon the Navier solution approach. Numerical results are provided in order to investigate the influences of various parameters including the nondimensional nonlocal parameter, type of transverse loading, temperature change, applied voltage, and external magnetic potential on the mechanical behaviors of METE nanoplates. Furthermore, comparisons are made between the results predicted by different nonlocal plate models by utilizing the developed unified nonlocal plate model and selecting the associated shape functions. It is illustrated that by using the presented unified nonlocal plate model, the development of a nonlocal plate model based upon any existing higher-order shear deformable plate theory is a simple task.